'Financial stability' safeguarding: modelling the Russian budgetary policy. (2019) - Pilipenko, Andrey I.; Dikhtiar, Vasily I.; Baranova, Nina M.
This article represents the attempt to formalise evaluation of the public fiscal policy impact on the financial stability of Russian economy. The problem of the direct relationship between financial stability as a kind of public goods and budgetary consolidation in connection with safeguarding it by the government has not been solved. The case of Russia has been taken because its economic dynamics leg twice behind the world economy with its 2.5-3%' growth rates in the short term and the western sanctions against the Russian Federation objectively put forward the necessity for researchers and politicians to investigate the problem of financial stability safeguarding of the country, isolated from the global division of labour. In this case the Russian budgetary and tax policy' modelling turns out to be very promising for fiscal policy-making as to its impact' evaluation on financial stability safeguarding. To reinforce the findings, some results associated with other theoretical investigations and analytical researches are presented.